Kurikulum Muatan Lokal Tingkat SMA Di Kalimantan Tengah - Reddy Siram (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2016)
Size of Central Kalimantan province, which reached 153.8 thousand square km or (1.5 times the island of Java) with a population of 2.3 million people plus natural resource conditions are very good at doing farming activities, especially rubber and rattan, make Central Kalimantan the distinctive characteristics as one of the province's largest rubber producer and rattan in Indonesia. Given the potential of the area is so large in relation to agricultural activity rubber and rattan, and also based on the opportunity for students who are limited to continue on to higher education (college), then it should be in the schools in the area needs to be the development of a local curriculum that adapted to the natural conditions and potentials. To that end, at the Senior High School in Central Kalimantan needs to be a local curriculum that refers to the way agricultural cultivation skills of rubber and rattan as a way to preserve the culture of indigenous farming in Central Kalimantan. This study aims to generate local curriculum level of high school, especially for the field of agricultural skills planting rubber and cane that can be applied to the entire Senior High School in the province of Central Kalimantan and found a number of factors that may affect the implementation of the development of local content in school curriculum Senior High School in the province of Central Kalimantan.